Decrease of the Incidence of Renin-Angiotensin-System Inhibitor Induced Oligohydramnios-Sequence in Germany in 2011 - Hünseler, C.; von Kries, R.; Roth, B. (Klinische Pädiatrie, 2014)
to assess whether the incidence of angiotensin II-receptor type 1antagonist (AT1-antagonist) – or ACE-inhibitor induced cases of oligohydramnios sequence (OHS) in 2011 was reduced after intensive alerts as to the causal association between AT1-antagonist /ACE-inhibitor and OHS in the German medical literature.3 sources of information were used: A nationwide active surveillance of OHS in German paediatric hospitals (ESPED); Embryotox, (Berlin Institute for Clinical Teratology and Drug Risk Assessment in Pregnancy) and screening of pubmed (AT1-antagonist/ACE-inhibitor induced OHS).45 cases of OHS were identified, no case due to maternal AT1-antagonist/ACE-inhibitor treatment. Causes for OHS were: premature rupture of membranes (PPROM) (n=28), congenital anomalies of fetal kidneys and urinary tract (CAKUT (n=15), placental insufficiency (n=1), unknown cause (n=1). Mortality until discharge was 37.8% (32.1% PPROM, 57.1% CAKUT). Embryotox identified 3 exposures to AT1-antagonists in pregnancy, no case was associated with OHS. The pubmed search did not identify any case of OHS related to AT1-antagonist/ACE-inhibitor in pregnancy in Germany in 2011.Treatment of pregnant women with ACE inhibitors or AT1-antagonists still occurs but no cases of AT1-antagonist- or ACE-inhibitor induced OHS were reported in 2011 in Germany most likely due to repeated published alerts underlining the importance of consequent education. OHS remains a serious condition with high mortality despite modern intensive care.
Keywords: oligohydramnios sequence; angiotensin II-receptor-antagonist; ACEinhibitor; newborn; ESPED